Massively parallel sequencing is unlocking the potential of environmental trace evidence. (January 2021) - Young, J.M.; Linacre, A.
Highlights: Highlights the ability of MPS to complement and enhance current forensic ecology and human identification tools. Provides an overview of key studies that explore the use of environmental DNA (eDNA) from high and low biomass samples in a forensic context. Describes recent key developments in evidence evaluation that are leading the integration of eDNA techniques into forensic casework. Discusses the current inconsistencies in eDNA reporting and the required validation criteria for eDNA to be fully accepted in court. Abstract: Massively parallel sequencing (MPS) has revolutionised the field of genomics enabling substantial advances in human DNA profiling. Further, the advent of MPS now allows biological signatures to be obtained from complex DNA mixtures and trace amounts of low biomass samples. Environmental samples serve as ideal forms of contact trace evidence as detection at a scene can establish a link between a suspect, location and victim. Many studies have applied MPS technology to characterise the biodiversity within high biomass environmental samples (such as soil and water) to address questions related to ecology, conservation, climate change and human health. However, translation of these tools to forensic science remains in its infancy, due in part to the merging of traditional forensic ecology practices with unfamiliar DNA technologies and complex datasets. In addition, people and objects also carry low biomass environmental signals which have recently been shown to reflect a specific individual or location. The sensitivity, and reducing cost, of MPS is now unlocking the power of both high and low biomass environmental DNA (eDNA) samples as useful sources of genetic information in forensic science. This paper discusses the potential of eDNA to forensic science by reviewing the most explored applications that are leading the integration of this technology into the field. We introduce novel areas of forensic ecology that could also benefit from these tools with a focus on linking a suspect to a scene or establishing provenance of an unknown sample and discuss the current limitations and validation recommendations to achieve translation of eDNA into casework.